LAS ESTRATEGIAS LÚDICAS Y LA CONVIVENCIA EN EL AULA DE LOS NIÑOS DE PRIMER GRADO DE LA UNIDAD EDUCATIVA INTERCULTURAL BILINGÜE “CORAZÓN DE LA PATRIA” DE LA PARROQUIA LIZARZABURO, CANTÓN RIOBAMBA, PROVINCIA DE CHIMBORAZO, PERÍODO LECTIVO 2013 -2014 - Guamán Tenemasa, Luz María (2016)
The topic called: Ludic strategies inside the classroom of the first year students of basic education in the "Corazón de la Patria" school was developed to solidify the learning environment as well as to acquire new interactive strategies to promote their own acceptance and other members of the institution. By educating people on interpersonal relationships from the beginning, it helps to avoid problems that can appear in the future, giving the students the chance of being the main actor in their own integral development. To reach this goal, a proposal was applied which responds to the need to transform the institution mentioned above, in a pleasant, dynamic and productive environment, taking advantage from motivation as a resource to acquire knowledge. Games let people experience reality, that is to say, these constitute a way of physical, spiritual and mental satisfaction. The ludic strategies in the first year students of basic education foster a variety of ethical and moral values that help them build an analytic, critical and reflexive personality. A better school environment, discipline and respect to individual differences were the obtained results throughout the present study.